Adaptive Control Schemes for a class of Hammerstein-Wiener nonlinear systems - AL-Sunni, Fouad (2020)
In this work we develop two different adaptive control schemes for a class of nonlinear systems. The class of systems belongs to the Hammerstein-Wiener nonlinear systems. The techniques developed are presented and an example is given in illustration. Using an approximate inverse of the nonlinear plant model, the overall system is forced to track the desired reference signal. Keywords: nonlinear systems, adaptive control precompensation, Hammerstein-Wiener systems.